A phase I study of extended dosing with lomeguatrib with temozolomide in patients with advanced melanoma - Kefford, R F (Nature Publishing Group, 2009)
Lomeguatrib, an O(6)-methylguanine-DNA methyltransferase inactivator, was evaluated in an extended dosing regimen with temozolomide, designed according to pharmacodynamic data from previous studies. Patients with unresectable stage 3 or 4 cutaneous or unknown primary melanoma metastases were treated with lomeguatrib 40 mg, b.i.d. for 10 or 14 days and temozolomide 75–100 mg m(−2) on days 1–5. Drugs were administered orally with cycles repeated every 28 days, for up to six cycles. A total of 32 patients were recruited to the study. Lomeguatrib for 10 days with temozolomide 75 mg m(−2) was established as the optimal extended lomeguatrib dosing schedule, with haematological toxicity being dose limiting. There were two partial responses to treatment giving an overall response rate of 6.25%. Extending lomeguatrib administration beyond that of temozolomide requires a reduced dose of the latter agent. Only limited clinical activity was seen, suggesting no advantage for this regimen over conventional temozolomide administration in the treatment of melanoma.